Analisis Faktor Risiko Kejadian Musculoskletal Disorders (MSDS) Pada Pekerja Officer dan Welder Menggunakan Metode Nordic Body Map di PT XYZ Kota Batam - Chinta Yolanda Sari (Jurnal Liga Ilmu Serantau, 2024)
Musculoskeletal Disorders (MSDs) are among the occupational hazards characterized by complaints in the muscle area. MSDS occurs due to incorrect body posture during work, leading to excessive muscle strain over prolonged periods. PT.XYZ is a company operating in the engineering contractor field across various industries and sectors, with workers in several departments including officers and welders. These workers are susceptible to MSDS due to various factors. This study aims to analyze the risk factors for MSDS incidence among officers and welders at PT.XYZ. The research is descriptive analytics involving the entire population of 30 workers in the officer and welder departments. The sampling technique used was saturation sampling, utilizing both primary and secondary data sources. Data collection methods included field observations, questionnaires, and interviews. Research instruments comprised a checklist using the Nordic Body Map (NBM), questionnaire items, and interview guidelines. Results: The study revealed significant associations between tenure, length of service, work attitude, and MSDS incidence. Simple logistic regression analysis indicated that tenure had a p-value of 0.027 and OR of 10.00 with a 95% CI of (0.994-100.612). The p-value for length of service was 0.010 with an OR CI 95% of 13.71 (1.381-136.212), while work attitude had a p-value of 0.003 with a 95% CI of (1.879-185.399). The findings emphasize the importance of addressing tenure, length of service, and work attitude to reduce MSDS incidence among officers and welders. Implementation of ergonomic interventions and promotion of proper workplace posture may help reduce the risk of MSDS in this group of workers.